REASONS OF DIVORCE AND THEIR SOCIO-PHILOSOPHICAL ANALYSIS - Dildora Mirakbarova (Galaxy International Interdisciplinary Research Journal, 2021)
This article emphasizes that a happy and strong family is the basis of every society, only when the family is spiritually happy, material benefits are visible, demographic problems are solved and everyone can make a peaceful contribution to the development of their industry. The article examines the reasons for divorce, its secular and religious analysis. In addition, the fate and opinions of experts and divorced young people were studied through questionnaires and interview methods, and appropriate conclusions were drawn. It has been shown that the ability to study, analyze and draw the right conclusions from the problems that undermine the stability of the family, the causes of divorce, leads to a prosperous future of the family and society.